Afinidad fitogeográfica y papel sucesional de la flora leñosa de los bosques de pino‑encino de los Altos de Chiapas, México - Quintana-Ascencio, Pedro F.; Gonzalez-Espinosa, Mario (Instituto de Ecología, A.C., 1993)
A successional role for each phytogeographical group of seral stands of the pine-oak forests in the Highlands of Chiapas (southern Mexico) could be established after their structural analysis. Most of the Holarctic elements regenerate in early successional conditions, while the regeneration of many Andean and East Asian elements is restricted to the more advanced stands. Forest structure and floristic composition appears as the result of a mixture of species belonging to genera of diverse origin. Their local coexistence seems to depend on their tolerance to those environmental conditions resulting from forest development through succession. We ascribe a central role to the canopy species belonging to Holarctic genera which determine the understory microhabitat for most of the remaining woody species, notably for those of Andean affinity.